The process of client data integration - Ostojić, Josip (Array, 2008)
The paper describes the process model of client data integration in an insurance company information system. Basic business processes in insurance companies sales and damage are the key source of data on clients. The process of business information system integration is necessarily accompanied by the process of client data integration, as the basic entity type, i.e. the central table in the database. The decomposition of process integration was conducted and the activities of a given stage are described in detail. The process was applied and tested on damage applications and insurance sales applications. The process of client data integration is decomposed into three stages: analysis, preparation and integration. Each stage consists of more than one activity, and certain activities are further decomposed. A central place or a client database needs to be created in order to serve as a data source on clients for all application systems.